Industrialización de la Jícama (smallanthus sonchifolia), Jicamte - Chicaiza Toapanta, Gabriela Lisset (2017)
The objective of the present research project was to obtain a tea from the jicama leaf (Smalanthus sonchifolia) by the mechanical drying method using a tray dehydrator. The dehydration process consists of three factors: temperature (30ºC and 40ºC), time (10h and 12h), thickness (2cm and 4cm), focused on the industrialization of agricultural products intended for all types of consumers in the Latacunga city. The research was carried out in the Laboratories of Research of the Race of Agroindustrial Engineering. Jicama leaf tea (Smalanthus sonchifolia) underwent chemical and sensory analysis to obtain the best treatment with which ADEVA (AxBxC) showed that the best treatment was t8 (a2b2c2) with Combination of 40ºC of temperature, 12h of dehydration time and 4cm of thickness of the material, with the following values (initial humidity 88,50%, final humidity 7,04%, total ashes 7,18%, and as for color between very pleased and slightly liked, aroma between very intense and intens, acceptability between likes and dislikes. The percentages obtained from each of the quantitative variables according to the physical chemical and microbiological analysis of the best treatment indicate that the tea of jicama leaf is within the limits established by the norm INEN 2381 being a product suitable for human consumption. These percentages were determined in the food, water and related analysis laboratory (LABOLAB). To conclude the dehydration process, the jicama leaf was placed in teapot paper bags and the price per 3g, is 0.10 ctvs.